Effect of Silver content on the Optical and Other Physical Characteristics of Ge-Se Glass System - Tiwari, Saurabh; Kumar Saxena, Ashish; Saxena, Dinesh (Asian Journal of Chemistry, 2011)
The effect on the optical and other physical properties with the addition of Ag content, viz, Tg, <E>, Hs, <reff> , Z, Ncon, L, ΔEg and energetic parameter A of Ge30-xSe70Agx (x = 0, 5, 10, 15, 20 at %) glassy alloy have been examined theoretically. The relationship between the Tg and has been estimated by using Tichy-Ticha approach. The relationship between ΔEg and chemical composition has been discussed in terms of the Hs and Z. In order to correlate the optical parameter (ΔEg) with film composition we used the energetic parameter (A). It has been found that , Hs, (ΔEg), Tg, decreases whereas deviation of stoichiometry R, Ncon and the energetic parameter A, increases with increasing Ag content in Ge-Se-Ag system.